Rewriting the Future: Tessa Boffin's The Knight's Move - Flora Dunster (British Art Studies)
This article focuses on the practice of the late photographer Tessa Boffin. I situate her work in the context of British art and politics as they were at the time of "queer" being reclaimed from a term of abuse in the late 1980s and early 1990s, and explore how she used photography to visualise what "queer" could mean from a lesbian perspective. The article centres on an analysis of Boffin's series *The Knight's Move* (1990), in which she rewrites the history of her queer present to include a lesbian past. While these photographs can be viewed as a precedent for an intersectional and exploratory understanding of queerness, I suggest that "the knight's move" can also work beyond the series itself. I locate it as a strategy for bringing "queer" and "lesbian" together in our present, re-figuring both positions in relation to each other and in resistance to the gatekeeping around the meaning of each word. I argue for the knight's move as a device that allows us to situate photographs not as historical remnants but as a vital site of community formation, thereby offering a way of working *with* Boffin's oeuvre rather than *on* it.